(untitled) (Research, Society and Development, 2025)
The study addresses the vulnerability of Munduruku Indigenous adults to HIV, focusing on the Kainã Village, located in the Amazon region. The general objective was to develop integrated and culturally sensitive educational actions that would strengthen knowledge about prevention and reduce stigma. The methodology of this study was based on a qualitative, descriptive, and participatory approach, developed through an outreach project in Kainã Village, inhabited by the Munduruku ethnic group and located in the Amazon region. The research is limited to promoting HIV prevention through health education and the appreciation of traditional knowledge. The results of data collection conducted in Kainã Village, which included 21 Indigenous adults—5 men (24%) and 16 women (76%) from the Munduruku group—showed increased knowledge about HIV, satisfactory adherence to preventive practices, and strengthened community engagement. The actions integrated biomedical knowledge with Indigenous wisdom, promoting comprehensive and sustainable care. It is concluded that intercultural educational strategies are essential to reduce vulnerabilities and strengthen health promotion among Amazonian Indigenous peoples.